Biomarker recommendation for PD‐1/PD‐L1 immunotherapy development in pediatric cancer based on digital image analysis of PD‐L1 and immune cells. (10th January 2020) - Silva, Manuel A; Triltsch, Nicolas; Leis, Simon; Kanchev, Ivan; Tan, Tze Heng; Van Peel, Benjamine; Van Kerckhoven, Marian; Deschoolmeester, Vanessa; Zimmermann, Johannes
Abstract: Anti‐PD‐1/PD‐L1 immunotherapy could offer an alternative to traditional chemo‐ and/or radiotherapy to treat pediatric cancer patients. To unveil the potential benefit of this new therapeutic approach, the prevalence of PD‐L1 and other relevant immune markers using quantitative digital image analysis (DIA) could help to clarify this point. A bridging study was first conducted using commercially available normal formalin‐fixed paraffin‐embedded (FFPE) tonsils to compare immunostaining patterns and intensities from PD‐L1, tumor infiltrating lymphocyte (TIL) markers CD3, CD8, FoxP3, CD45RO, and macrophage marker CD68 in adult ( n = 5) and pediatric ( n = 10) samples. Then, commercially available pediatric FFPE tumor samples from five prevalent pediatric solid tumor indications: ganglioneuroblastoma ( n = 7); neuroblastoma ( n = 23); nephroblastoma ( n = 30); osteosarcoma ( n = 24); and rhabdomyosarcoma ( n = 25) were immunostained and their images ( n = 654) digitally analyzed using predefined algorithms. The qualitative analysis of staining patterns and intensities in all 15 tonsils for all 6 biomarkers was similar regardless of age category. Quantitative DIA showed that PD‐L1 values varied across cancer‐types, nephroblastoma having the lowest counts. PD‐L1 counts in ganglioneuroblastoma, our pediatric indication with the highest average value, was approximately 12‐times lower than in a similar nonsmall cell lung cancer study, an indication approved for anti‐PD‐1/PD‐L1 immunotherapies. Variable values were measured for the TIL markers CD3, CD8, and CD45RO. FoxP3 was scant across all indications. The macrophage marker CD68 showed highest values in ganglioneuroblastoma, with lowest levels in nephroblastoma. In conclusion, the low PD‐L1 levels uncorrelated with TIL values from the present biomarker morphological study suggest that a PD‐L1 immunohistochemistry patient selection strategy used for anti‐PD‐1/PD‐L1 monotherapy in adult tumors may not succeed in these pediatric indications.